A Prekindergarten Curriculum Supplement for Enhancing Mainstream American English Knowledge in Nonmainstream American English Speakers - Edwards, Jan R. (Lang Speech Hear Serv Sch, 2016)
PURPOSE: The purpose of this study was to evaluate the efficacy of a curriculum supplement designed to enhance awareness of Mainstream American English (MAE) in African American English- (AAE-) speaking prekindergarten children. METHOD: Children in 2 Head Start classrooms participated in the study. The experimental classroom received the Talking and Learning for Kindergarten program (Edwards, Rosin, Gross, & Chen, 2013), which used contrastive analysis to highlight morphological, phonological, and pragmatic differences between MAE and AAE. The control classroom received the Kindness Curriculum (Flook, Goldberg, Pinger, & Davidson, 2014), which was designed to promote mindfulness and emotional self-regulation. The amount of instruction was the same across the 2 programs. Both classrooms participated in pre- and posttest assessments. RESULTS: Children in the experimental classroom, but not the control classroom, showed significant improvement in 3 norm-referenced measures of phonological awareness and in an experimental measure that evaluated comprehension of words that are ambiguous in AAE, but unambiguous in MAE, because of morphological and phonological differences between the 2 dialects. CONCLUSION: Although more research needs to be done on the efficacy of the Talking and Learning for Kindergarten program, these results suggest that it is possible to enhance AAE-speaking children's awareness of MAE prior to kindergarten entry.